Design of Advanced Process Control Strategy for Industrial Pressure Process (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the process industry, pressure process control is important. Pressure process control systems have been refined and used in numerous implementations of in several process industries, pressure process plants are used, including chemical process industries, pharmaceuticals, wastewater treatment, and power plants. Pressure process management is essential in the process industry. Pressure process control systems have been refined and applied to a wide range of pressure process plant applications in a number of industries, including chemical manufacturing, pharmaceuticals, wastewater treatment, and power plants. The execution of such mechanism may result in remote and then the parameters can change over time.